1985
DOI: 10.1095/biolreprod33.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Major Contribution of Epididymis to α-Glucosidase Content of Ram Seminal Plasma1

Abstract: Acid alpha-glucosidase and L-carnitine (a well-known epididymal marker) were measured in rete testis and epididymal fluids of adult male rams. These fluids were collected by selective catheterization or by a micropuncture technique, respectively. Both parameters remained at a low and constant level in rete testis and all along caput and corpus epididymidis. Then they increased at equivalent rates in cauda epididymidis to much higher levels than those in seminal plasma (5 mU/mg protein and 10 mM, respectively).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Indeed, whereas the carnitine levels began to increase in the fluid in the distal caput epididymidis (regions 3-4), the carnitine content of spermatozoa did not rise until the cells had reached the distal corpus (regions 6-7). An increase in the carnitine amount of the epididymal fluid has already been demon¬ strated in different species (Hinton et al, 1979;Besançon et al, 1985). Our results relative to the caudal epididymal fluid of the boar as expressed in µ /ml (Table 1) are similar to those obtained by Hinton et al (1979) for the same region (15-20mM), although we found a higher carnitine concentration gradient.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, whereas the carnitine levels began to increase in the fluid in the distal caput epididymidis (regions 3-4), the carnitine content of spermatozoa did not rise until the cells had reached the distal corpus (regions 6-7). An increase in the carnitine amount of the epididymal fluid has already been demon¬ strated in different species (Hinton et al, 1979;Besançon et al, 1985). Our results relative to the caudal epididymal fluid of the boar as expressed in µ /ml (Table 1) are similar to those obtained by Hinton et al (1979) for the same region (15-20mM), although we found a higher carnitine concentration gradient.…”
Section: Discussionsupporting
confidence: 89%
“…After the first rise, the carnitine concentration shows only slight gradual increase along the epididymis in the hamster, rabbit and boar (Hinton et al, 1979), but a 3-fold increase has been found in the rat (Hinton et al, 1979), and an 8-fold increase in the ram (Besançon et al, 1985). The origin of acetylcarnitine in the epididymal fluid is unclear.…”
Section: Introductionmentioning
confidence: 98%
“…It is interesting to note that alpha-glucosidase activity is absent from the mice and hamster epididymis, whilst in monkey semen enzyme activity is barely detectable. In contrast, there is high activity of alpha-glucosidase in the epididymis of the rat and ram (Besancon et al, 1985a;Yeung et al, 1990). Because the distribution of rat epididymal alpha-glucosidase is close to that of the human, this animal may be a suitable model in which to study the role of epididymal secretions, such as alpha-glucosidase, on the metabolic activity and fertilizing ability of spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore of interest to ascertain whether ram epididymal a-l,4-glucosidase was under androgenic control, be cause of our initial observations indicating a net increase of the enzyme in the seminal plasma of lambs progressing to sexual matu rity [4], We postulated that the optimal physiological condition to observe this puta tive hormonal influence was to determine the enzyme activity in relationship with the In 1985, Besançon et al [1] observed that the enzyme a-l,4-glucosidase was localized mainly in the caput epididymis of adult rams. This observation corroborated pre vious results from this laboratory indicating the presence of a-l,4-glucosidase in the cauda epididymis of men [2] and rats [3].…”
Section: Introductionmentioning
confidence: 99%
“…The role of this enzyme in the reproductive tract of mammals has been a matter of inter est for our group as mammalian spermato zoa are exposed to various epithelial secre tions of the seminiferous tubule and of the epididymal duct during their development. Among the variety of minor epididymal a-Glucosidase-Specific Activity and Testosterone Concentrations Seminal plasma a-glucosidase-specific activity and blood plasma testosterone concentration were measured according to the methods previously de scribed by Besançon et al [1,4], The inter-assay coef ficient of variation of the method for the a-glucosidase assay was 2 % after dozens of determinations in duplicate at weekly intervals. serum testosterone variations which exhibit typical seasonal variations in two breeds of rams.…”
Section: Introductionmentioning
confidence: 99%